Establishing of Conceptual Model of Separation of Waste at the Source (SAS) - Syukrie Mohd Nasir; Shafii, Haryati; Md Yassin, Azlina (International Journal of Sustainable Construction Engineering and Technology, 2022)
There is consensus that environmental issues are consequences of human activities and can be addressed by improvements in behavior. Separation of waste at the source (SAS) as mandated through Act 672 is a pro-environmental behavior (PEB) at the household level to reduce waste from being send to landfill and also an effective measure in reducing waste as a whole which will ultimately protect the environment from pollution. Based on the problem statement that lack of household knowledge on how to perform the separation of waste and holding environmental ethics that is not pro-environment will hinder household from performing such behavior, this article aims to establish a conceptual model of separation of waste at the source among households in Malaysia. The conceptual model proposed a modification to Value-Belief-Norm (VBN) model to predict SAS behavior with environmental ethics and specific waste separation knowledge as an adjustment and additional factors to the original model which could demonstrate the causal-effect relationship towards the behavior. The conceptual model proposed individuals with biocentric and ecocentric beliefs to be more likely to engage in SAS behavior than those with anthropocentric and technocentric beliefs. The conceptual model also proposed that individuals specific waste separation knowledge will moderate the relationship between personal norm and SAS behavior. It is expected that the conceptual model has a potential in helping researchers and stakeholders to better understand the underlying SAS behavior among households in Malaysia.